From labour market to labour process: finding a basis for curriculum in TVET*. (1st September 2016) - Gamble, Jeanne
Abstract: In the sociology of education the relation between education and work is analysed in many ways and, since the rise of neoliberalism, increasingly in market terms. Skills are the dominant labour market currency, described in terms of competence profiles that seek to link educational qualifications directly to work. Contrary to the widespread appeal of competence-based curriculum approaches, this paper argues that the vocationalist impulse of the neoliberal era impacts as negatively on technical and vocational education (TVET) as it does on general education in its destruction of a basis for curriculum that includes knowledge and not only skills. The paper draws on a recent empirical study of labour processes in four industry sectors in South Africa to show why work-related curricula need to foreground knowledge not just in terms of its applied qualities but as a necessary ingredient of technical systems complexity.